Nitrates and Nitrites in meat products - GOVARI (Μ. ΓΚΟΒΑΡΗ) M.; PEXARA (Α. ΠΕΞΑΡΑ) A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Nitrates and nitrites have been traditionally used as curing agents in the production of cured meat products. Beneficial effects of the addition of nitrates and nitrites to meat products are the improvement of quality characteristics as well as the microbiological safety. The nitrates and nitrites are mainly responsible for the development of the distinct flavor, the stability of the red color, as well as the protection against lipid oxidation in cured meat products. The nitrites show important bacteriostatic and bacteriocidal activity against several spoilage bacteria as well as foodborne pathogens found in meat products. The nitrites prevent the growth and toxin production by Clostridium botulinum. According to Commission Regulation (EU) No. 1129/2011, nitrates (sodium nitrate, E251; potassium nitrate, E252) and nitrites (potassium nitrite, E249; sodium nitrite, E250) are listed as permitted food additives. Nitrates are relatively non-toxic, but nitrites, and nitrites metabolic compounds such as nitric oxide and N-nitroso compounds, have raised concern over potential adverse health effects. Recently, the International Agency for Research on Cancer (IARC) concluded that ingested nitrates or nitrites are probable carcinogen to humans under conditions favoring the endogenous nitrosation. Legal limits for the addition of nitrates and nitrites have been set by several countries and EU [Commission Regulation (EU) No. 601/2014]. Several data from recent reviews conducted in several countries on the levels of nitrates and nitrites in cured meat products were summarized. In recent reviews, the residual levels of nitrites in cured meat samples have been constantly reduced and are in accordance with the legal limits set by most countries.